2009
DOI: 10.1176/appi.ps.60.5.617
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Switching Among Adherent Patients Treated for Depression

Abstract: Among adults with depression starting antidepressant therapy, medication switching commonly occurs during the first three months of treatment. Greater clinical severity and low initial dosing may increase the risk of switching antidepressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
3
12
2
Order By: Relevance
“…However, it is unclear if some of the differences observed here were due to the fact that duloxetine was still the newer antidepressant at this time and whether the observed factors would persist if later data was utilized. Greater clinical severity and low initial dosing have been found to be factors predicting earlier antidepressant switching [24] and such patients may have preferentially tried the newer medication. We did not assess initial dose in this work and additional confirmatory work utilizing more recent data is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear if some of the differences observed here were due to the fact that duloxetine was still the newer antidepressant at this time and whether the observed factors would persist if later data was utilized. Greater clinical severity and low initial dosing have been found to be factors predicting earlier antidepressant switching [24] and such patients may have preferentially tried the newer medication. We did not assess initial dose in this work and additional confirmatory work utilizing more recent data is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The classes of antidepressants used as first-line agents among patients starting treatment for a new episode of depression appear to be new generation ones in many parts of the world. In USA a nationally representative survey of medical service utilization between 1996 and 2001 indicated that 75% of patients who initiated antidepressant treatment for depression started with selective serotonin reuptake inhibitors (SSRIs) or serotonin and noradrenaline reuptake inhibitors (SNRIs) (Olfson et al, 2006), Medical and pharmacy claims database in more recent years also report similar figures (78% between 2001 and 2004 (Robinson et al, 2006), or 87% between 2001(Marcus et al, 2009). In Europe a cohort study of consecutive patients commencing antidepressant treatment at over 400 primary and secondary care clinics indicated that across 12 countries, 63% started with SSRIs and 14% with SNRIs (Bauer et al, 2008).…”
mentioning
confidence: 96%
“…However, the clinicians' actual behaviors may or may not be the same as what they say they do. For example, among patients who initiated antidepressant therapy and who continued treatment for more than 3 months, switching antidepressants took place only in 9% (Marcus et al, 2009). To the best of the present authors' knowledge no other study looked at how switching and other second-line strategies are employed in the clinical practices.…”
mentioning
confidence: 97%
“…The support for the predicted relationship between SLC6A4 and trimipramine stems from the similarity to the two drugs directly related to the gene, in the text-mining-derived network (mirtazapine and clomipramine), and from the similarity to the drug carbamazapine, which is related in the text-mining-derived network to the CALR gene, found to interact with SLC6A4 in the InWeb network. Mirtazapine is an antidepressant used for the treatment of moderate to severe depression, and has a very similar set of indications as trimipramine 18 . Of the drugs that co-occur in the literature with SLC6A4, the one that is most similar in structure to trimipramine is clomipramine.…”
Section: Resultsmentioning
confidence: 99%